2022
DOI: 10.3389/fphy.2022.919787
|View full text |Cite
|
Sign up to set email alerts
|

Application of a scattering foil to increase beam transmission for cyclotron based proton therapy facilities

Abstract: In proton therapy, high dose rates can reduce treatment delivery times, allowing for efficient mitigation of tumor motion, as well as increased treatment efficiency and patient throughput. In cyclotron-based facilities, however, high dose rates are difficult to achieve at low-energies. In current facilities, the emittance after the degrader is matched in both transversal planes using circular collimators; this does not provide an optimal matching to the acceptance of the following beamline. However, transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Currently, all cyclotron-based proton therapy facilities transport a maximum emittance of 30 π mm mrad through the beamline (in this work, beam sizes, divergences, and emittances are expressed as 2σ values), which limits the transmission of low-energy beams. At PSI for example, for the lowest energies (70-100 MeV), transmission through the beamline is below 0.1 % [8]. Such low transmission for these low energies causes an increase in beam-on time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, all cyclotron-based proton therapy facilities transport a maximum emittance of 30 π mm mrad through the beamline (in this work, beam sizes, divergences, and emittances are expressed as 2σ values), which limits the transmission of low-energy beams. At PSI for example, for the lowest energies (70-100 MeV), transmission through the beamline is below 0.1 % [8]. Such low transmission for these low energies causes an increase in beam-on time.…”
Section: Introductionmentioning
confidence: 99%
“…One way to achieve higher intensity beams at the isocenter is to transport a higher emittance through the following beamline and gantry [8][9][10][11]. At our facility, we can transport a maximum of ~65 π mm mrad in X-plane and ~139 π mm mrad in Y-plane.…”
Section: Introductionmentioning
confidence: 99%
“…17 A recent study has demonstrated a concept of incorporating a momentum cooling design in the energy selection system to reduce the momentum spread of the beam without introducing substantial beam losses, which allows delivering proton beams at FLASH dose rates, while maintaining the necessary energy modulation. 18 To achieve FLASH delivery without modifying the current cyclotron gantry design,a potential solution is to utilize the highest energy beam for FLASH planning, bypassing the need for the inefficient energy modulation system. Efforts have been made to employ high-energy proton transmission beams (TBs) to cover the target with the entrance dose region while delivering BPs outside the patient, demonstrating feasibility in attaining the FLASH effect.…”
Section: Introductionmentioning
confidence: 99%
“…At PSI, for example, for the highest energies (200-230 MeV), transmission through the beamline is about 30 %. However, for the lowest energies (70-100 MeV), transmission through the beamline is below 0.1 % [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%